Uma proposta didática de ensino de ondas auxliada pela construção de um tubo de kundt - Nunes, Raimundo Helison Gilo (2019)
The respective work reports the search for learning tools through the construction and applicability of experiments by students and respective presentation in the classroom. The proposal was applied in a group of the second year of high school of the Patronato school and had the participation of 25 students. It was carried out a preliminary analysis of the dissertations of articles and dissertations of some universities, that deal with experiments of physics for the high school, Federal University of. (UFRN) and Federal University of. Rio de Janeiro (UFRJ). He pointed out the Significant Learning of David Ausubel and Vygotsky's interactionist socialist perspective in relation to the experiments of Physics as theoretical referents more approached tied with Motivation. In the collected data, we used: Lectures with extra class activities for resolution before and after the construction of the experiment, experimental scripts, questionnaires, previous test and final test, with "safety degree" of the given answers and student evaluation. The respective work had a qualitative and quantitative analysis, where the results obtained by the data collection were quite significant after the use of the construction proposal of the experiment, as well as the application of new concepts of greater conceptual relevance. The final test had a very fruitful number of hits and the degree of safety of the content revealed that the students were more sure of the answers they got right. In the applied evaluation questionnaire there was an increase in the grade given to the students by the teacher, reflecting a motivating activity. We can say that the proposal of construction of the experiment, also called intervention, was successful, for the concepts related to acoustics, especially the standing waves.